Health Research in Developing Countries: A collaboration between Burkina Faso and Germany - Becher, Heiko; Kouyaté, Bocar (SpringerLink Bücher, 2005)
Health research in developing countries has many facets. On one side, malaria and AIDS as main causes of morbidity and mortality are a focus for clinical and epidemiological studies. On the other side, the need for improving the health care system in general cannot be overestimated. The book offers a survey of current and important topics of health research in developing countries. Special emphasis is placed to show that cooperation of different health research areas if of highest importance in future. In addition the CRSN (Burkina Faso) - University of Heidelberg collaboration is given as a model that allows high class research in remote areas of any developing country. An absolutely must for all who are working in clinical, epidemiological and health systems research for and in developing countries.